Laser in urology: experience in Hospital Universiti Kebangsaan Malaysia - Ab Rashid, Islah Munjih; JM, Nazri; MZ, Zulkifli; B, Badrulhisham; S, Sritharan; Lee, BC (2005)
BACKGROUND Recenta dvancesin technologyh ave an impact in urology. Laser is now a widely acceptedto ol in urology especiallyi n the field of endourologyI.t hast he advantage of flexibility which allows easym anipulatione speciallyi n areaso f difficult access. AIM To auditr etrospectivelyth e outcomeo f lasert reatmentin variousu rologicalo perations performed in our center from January 2003 to October 2005. MATBRIALAND METHODS 77 patients underwent various urological operations in which laser was used from January 2003 till October 2005. The record of each patient was traced and analysed. The stonec learanced, iagnosis,t ype of operation,o perationt ime and complication were the variables and outcome studied. RESULTS Laserw asu sedi n thef ollowing cases5: 8 URS,5 RIRS, 10P CNL,2 vesicolithotripsy, 1 in removal of urethral stone and I in ureteral polyp ablation. Out of 77 patients, 49 had complete clearance of stone, 8 almost complete clearance, l9 partial clearance and only I failure due to technical difficulty. The complicationse ncounteredi n our series were ureteral perforation and ureteral stricture which occured in 5 patients. CONCLUSION The availabilityo f laseri n urology hasm ade endoscopicm anagemenot f urological diseasefe asiblee veni n areaso f difficult accessT. he outcomeo f lasert reatmenti n urologyi s good,e speciallyin managemenot f stoned iseasesC. omplicationsa rer are and it should be a preferred urological tool whenever indicated